Post-cardiac injury syndrome following permanent pacemaker implantation presenting exclusively as massive pleural effusion —A rare occurrence - Khalid, Nasiha; Rana, Ikram Ahmed (Journal of the Pakistan Medical Association, 2023)
Post-Cardiac Injury Syndrome (PCIS) akin to Dressler’s syndrome is late-onset pericarditis that is triggered by the body’s immune system and presents commonly as pleuro-pericardial symptoms and raised inflammatory markers. Its occurrence following the insertion of a pacemaker has been reported infrequently and varies in different studies with an estimated prevalence of 1-2%. Our case reports a unique incidence of isolated pleural effusion following the implantation of a pacemaker in a 62-year-old female with complete heart block with no evidence of pericardial effusion on imaging. She developed dyspnoea, pleuritic chest pain, and lethargy. She successfully responded to treatment with NSAIDs and colchicine with no recurrence. This report demonstrates the uncommon course of the disease and highlights the need to consider PCIS as a possible diagnosis in patients presenting with predominant pulmonary findings and suspect it early so that timely treatment can be started, thereby preventing complications.